2022
DOI: 10.3389/fnut.2022.861533
|View full text |Cite
|
Sign up to set email alerts
|

A Cocoa Diet Can Partially Attenuate the Alterations in Microbiota and Mucosal Immunity Induced by a Single Session of Intensive Exercise in Rats

Abstract: BackgroundFollowing intensive sports events, a higher rate of upper respiratory tract infections and the appearance of gastrointestinal symptomatology have been reported. We aimed to evaluate the effect of a cocoa-enriched diet on the cecal microbiota and mucosal immune system of rats submitted to high-intensity acute exercise, as well as to elucidate the involvement of cocoa fiber in such effects.MethodsWistar rats were fed either a standard diet, a diet containing 10% cocoa providing 5% fiber and a diet cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…Firstly, considering the exercise performance, we did not observe an improvement after 6 weeks of nutritional interventions with cocoa or cocoa plus hesperidin. This result agrees with most of the preclinical and clinical studies involving cocoa products, such as cocoa powder [ 38 , 42 , 49 ], cocoa flavanol capsules [ 37 ] or chocolate [ 36 , 50 , 51 ]. With regard to hesperidin, both preclinical [ 40 , 41 , 43 ] and clinical studies [ 35 , 39 , 52 , 53 ] have reported its ergogenic effects.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Firstly, considering the exercise performance, we did not observe an improvement after 6 weeks of nutritional interventions with cocoa or cocoa plus hesperidin. This result agrees with most of the preclinical and clinical studies involving cocoa products, such as cocoa powder [ 38 , 42 , 49 ], cocoa flavanol capsules [ 37 ] or chocolate [ 36 , 50 , 51 ]. With regard to hesperidin, both preclinical [ 40 , 41 , 43 ] and clinical studies [ 35 , 39 , 52 , 53 ] have reported its ergogenic effects.…”
Section: Discussionsupporting
confidence: 89%
“…Preclinical and clinical studies have associated both cocoa and hesperidin consumption with reduced oxidative stress after exercise [ 36 , 37 , 38 , 39 , 40 , 41 ]. Moreover, cocoa has shown interesting effects on the mucosal immunity and the gut microbiota in a rat model of acute intensive exercise, which was partially mediated by its fiber content [ 42 ]. We have also demonstrated the ergogenic and immunomodulatory effects of hesperidin supplementation in a preclinical model of exhausting exercise [ 40 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that hesperidin supplementation, which is the main polyphenol found in citrus fruits, was able to prevent the overproduction of ROS induced by exhausting exercise through enhancing the endogenous antioxidant systems of intensively trained rats [33]. Moreover, we recently found the beneficial effects of cocoa, especially from its fiber content, on the cecal microbiota and the mucosal immune system of rats submitted to acute exercise [34]. Here, we aimed to evaluate the effect of a cocoa-enriched diet on the physical performance, the ROS production by peritoneal macrophages, and the systemic immune function of rats submitted to intensive acute exercise, as well as to elucidate the involvement of cocoa fiber in such effects.…”
Section: Introductionmentioning
confidence: 99%
“…The previous effects observed by the polyphenols interventions on particular bacteria groups, such as Clostridium coccoides/Eubacterium rectale, Bifidobacterium and Lactobacillus/Enterococcus, led us to evaluate the changes induced by exercise only on these populations. For that, sequencing was initially discarded and targeted fluorescence in situ hybridization coupled to flow cytometry (FISH-FCM) as previously used in our group [ 48 ], was used. Group-specific fluorochrome-conjugated probes (Erec482 5′-GCTTCTTAGTCARGTACCG, Bif164 5′-CATCCGGCATTACCACCC, and Lab158 5′-GGTATTAGCAYCTGTTTCCA) (Sigma-Aldrich, Madrid, Spain), which hybridize the bacterial 16S RNA of each particular group were used.…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of IgA-coated bacteria (IgA-CB) in CC was determined by FCM as previously described [ 48 ]. The CC homogenate was stained with rabbit anti-rat Ig polyclonal antibody conjugated to fluorescein isothiocyanate (FITC) (Abcam, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%